Musykilatu Ta’limi Mahaarati Al-Qiraati min’Awaamili ghairu Al-Lughawiyyati wa Hululiha Fii Ta’liimi Al-Lughati Al-‘Arabiyati Fii Madarasah Al-Insan Al-Ibda’iyah - muharomi, syahrul; Sanah, Siti (Program Studi Pendidikan bahasa Arab IAIN Langsa, 2024)
Problematics in Arabic language learning is a very important aspect to know in order to achieve the objectives of Arabic language learning effectively, this study aims of identifying and analyzing the problematics of learning maharah qira'ah (reading skills) in Arabic language learning at Insan Kreatif School from a non-linguistic point of view. The research method used in this study is a qualitative method with an analytic descriptive approach with (case study), data collection techniques in this study are observation, interview, and documentation. This study found that in addition to linguistic factors, there are a number of non-linguistic factors that play a significant role in the difficulties faced by students. These factors include low student motivation, lack of support from the family environment, limited supporting facilities and infrastructure, and the use of learning media that has not been optimized. Through observations and interviews with teachers and students, this study shows that by overcoming these non-linguistic barriers, the Arabic learning process can be significantly improved. The results of this study are expected to contribute in formulating more effective strategies to improve Arabic reading skills in similar schools. Keywords: reading skills, problems, non-linguistic.